Feasibility of simultaneous recording of cervical and ocular vestibular-evoked myogenic potentials via galvanic vestibular stimulation. (December 2013) - Chang, Chih-Ming; Young, Yi-Ho; Cheng, Po-Wen
Abstract Conclusion: Simultaneous galvanic vestibular stimulation (GVS)-cervical vestibular-evoked myogenic potential (cVEMP) and GVS-ocular (oVEMP) tests yielded similar information to that obtained in individual tests. Objective: This study compared the characteristic parameters of cVEMPs and oVEMPs via GVS between individual and simultaneous recording patterns in healthy and elderly subjects. Consequently, the effectiveness of simultaneous GVS-cVEMP and GVS-oVEMP tests was assessed. Methods: A total of 24 healthy and 16 elderly subjects were enrolled in this study. All participants underwent individual cVEMP, individual oVEMP, and simultaneous cVEMP and oVEMP testing via GVS mode in a random order. The response rates and characteristic parameters of cVEMPs and oVEMPs between individual and simultaneous tests, including latencies, intervals, and amplitudes, were measured. Results: The VEMP parameters, including latencies, intervals, and amplitudes, all demonstrated no significant differences between individual and simultaneous tests (p > 0.05, paired t test), either in healthy or elderly subjects. Pearson's correlation analyses also revealed significant positive correlations in all parameters between these two tests (p < 0.05).